Early single clinical experience with the new Figulla ASD Occluder for transcatheter closure of atrial septal defect in adults - AÇIKGÖZ, NUSRET; CANSEL, MEHMET; ÖZDEMİR, RAMAZAN; Acikgoz, Nusret; PEKDEMİR, HASAN; Yagmur, Julide; Tasolar, Hakan; ERMİŞ, NECİP; Kurtoglu, Ertugrul; Atas, Halil; ÖZDEMİR, Ramazan (My University, 2011)
Background. Recently, the Occlutech Figulla ASD Occluder (FSO) has been introduced for transcatheter closure of atrial septal defects. This device can be used for transcatheter closure of small as well as large atrial septal defects.